SIGNIFICANCE OF IMMUNOGENETIC PREDISPOSAL FOR CLINICAL COURSE OF MYASTHENIA - L. N. Bubnova (SPb RAACI, 2014)
Abstract. The aim of this work was to reveal novel criteria for prediction of clinical course in myasthenia, based on immunogenetic characteristics of the patients. Sixty-five patients with different clinical forms, various clinical course and severity of myasthenia were involved into the study. All the patients were subject to complete clinical and neurological examination, and all of them have undergone thymectomy, a histology of thymus has been performed. Immunogenetic studies included HLA class I typing (A and B loci), like as HLA class II typing (DRB* locus). A positive association was found between development of disorder and presence of HLAB8 antigen, HLA-DRB1*03, and their combination, thus allowing for suggesting these specificities as probable markers of genetic predisposition for myasthenia development. An HLA-B7 specificity may have a protective role in evolution of this disease. It was shown that clinical severity in myasthenia and degree of neuromuscular conductive disturbances were more expressed in the patients carrying HLA-B8 antigen and HLA-DRB1*03 allele. Evaluation of immunogenetic state at earlier stages of disorder allows of timely differential diagnostics and individual prediction of clinical variability in myasthenia patients.